Critical Discourse Analysis Model Teun A. van Dijk in the Lyrics of the Song 'Cabe-Cabean' by Tjahjadi/Ishak as a Medium for Social Education - Budi, Imanuel Setyo; Suandi, I Nengah; Sudiana, I Nyoman; Dewantara , I Putu Mas (Global Action and Education for Society, 2025)
This article aims to conduct a critical discourse analysis using Teun A. van Dijk's model to examine the lyrics of the song